Assessment of natural ventilation system for a typical residential house in Poland = Ocena działania wentylacji naturalnej w budynku mieszkalnym, wielorodzinnym - Antczak-Jarząbska, Romana; Krzaczek, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the research results of field measurements campaign of natural ventilation performance and effectiveness in a residential building. The building is located in the microclimate whose parameters differ significantly in relation to a representative weather station. The measurement system recorded climate parameters and the physical variables characterizing the air flow in the rooms within 14 days of the winter season.
Keywords: wentylacja naturalna; komfort cieplny; PMV; efekt kominowy; natural ventilation; CO2; concentration; microclimate; stack effect